Pengaruh Partisipasi Masyarakat Dan Transparansi Kebijakan Terhadap Hubungan Antara Pengetahuan Badan Permusyawaratan Desa (Bpd) Tentang Anggaran Dengan Pengawasan Keuangan Desa - Rusmianto Rusmianto; Maryani Maryani; Arif Makhsun (Politeknik Negeri Lampung, 2018)
The objective of this study is to know: (1) the influence of BPD Knowledge on budgets onvillage financial oversight (APBDesa); (2) the influence of interaction of Communityparticipation on the relationship between knowledge of BPD on budget and village financialoversight (APBDesa); (3) The Influence of Public Policy Transparency Interaction on therelationship between knowledge of BPD on budgets and village financial oversight(APBDesa) and (4) Influence of BPD Knowledge interaction on budget, communityparticipation, and transparency of public policy towards village financial oversight(APBDesa). This research was conducted by using the members of the Village ConsultativeBoard (BPD) villages in Waysulan Sub-district, South Lampung Regency (8 Villages) as itsobject. The hypothesis in this research was tested by using multiple analysis (multipleregression). The data processing is done with the help of SPSS statistical application.Hypothesis testing performed after multiple regression models are used free of violation ofclassical assumptions, so that the test results can be interpreted appropriately. Theconclusions can be drawn is that the knowledge of village consultative bodies (BPD) has asignificant positive effect on the level of village financial oversight, while publicparticipation, accountability, and transparency of public policy do not affect the relationshipbetween the knowledge of members of village consultative bodies (BPD) these threevariables (public participation, accountability, and transparency of public policy) directlyaffect the level of oversight of village financial management.